Honor Killings in the Twenty-First Century - Pope, N.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2012)
Thousands of women are murdered every year by close relatives for allegedly violating an unwritten social code or rebelling against the patriarchal order. The book examines the roots and evolution of honor-based violence, as well as the ongoing struggle to eradicate it worldwide.
Keywords: Political science; Political sociology; Ethnology—Middle East .; Crime—Sociological aspects; Social justice; Human rights; Sociology; Political Science; Political Sociology; Middle Eastern Culture; Crime and Society; Social Justice, Equality and Human Rights; Gender Studies